(untitled) (Jurnal Manajemen Bisnis, 2026)
This study aims to analyze the influence of Islamic financial literacy and risk perception on Generation Z’s decision to use Islamic mobile banking in Indonesia. Despite offering ease of transaction and compliance with Islamic principles, the adoption rate of Islamic mobile banking among Generation Z is still relatively low. This study uses a quantitative approach with a survey method of 100 respondents aged 18–28 years who actively use Islamic mobile banking and were determined through purposive sampling techniques. Data were collected online through Google Forms and analyzed using multiple linear regression. The results show that Islamic financial literacy and risk perception simultaneously have a significant effect on Generation Z’s decision to use Islamic mobile banking. These findings emphasize the importance of improving Islamic financial literacy and managing risk perception to encourage the adoption of Islamic mobile banking services.